Socialising children’s negative emotions in early education : adapting and validating a scale for teachers - Sabiha Üzüm; Rabia Filik; Hasibe Özlen Demircan (International Journal of Emotional Education)
This study aimed to adapt and examine the cross-cultural validity and reliability of the Coping with Children's Negative Emotions Scale - Teacher Version (CNNES-T), which assesses the levels of early childhood (EC) teachers' perception of their reactions towards young children's negative emotions. For this purpose, two studies were carried out. In Study-I, the scale is adapted using a team translation technique, and exploratory and confirmatory factor analyses conducted to investigate the factor structure of the adapted scale with a sample of 720 EC teachers. Study-I revealed that the scale's factor structure differed from the original version. In Study-II, the structure of the scale was analysed by considering internal consistency estimates and confirmed with an adequate model fit via confirmatory factor analysis with a sample of 358 EC teachers. Findings supported the two-factor model of CCNES-T in the Turkish context, consisting of 48 items with good internal consistency coefficients.